APLIKASI AKAD WAKALAH PADA PRODUK BSM E-MONEY DI BANK SYARIAH MANDIRI - Ida Yuhanida; Didah Durrotunnafisah (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2018)
The development of increasingly sophisticated technology, transactions do not need to bring cash, but nowadays the community has been facilitated by the existence of electronic money (E-Money). BSM E-Money is a product in the Bank Syariah Mandiri Bandung Branch Office Ahmad Yani, which is a prepaid card based on smart cards that can be used for various transactions. BSM E-Money products use the wakalah contract, but in its operation the wakalah contract on BSM E-Money products is not explained in detail in the product implementation instructions, it is feared that there will be misuse of the contract. The purpose of this study is to find out: 1) Application of wakalah contract in BSM E-Money products in Bank Syariah Mandiri. 2) Form and process of transaction of BSM E-Money products. 3) Relevance between the application of wakalah contract on BSM E-Money products at Bank Syariah Mandiri with Sharia Economic Law. The framework of thought of this research is based on the contract used in time with the rewards for BSM E-Money products including the contract contract in terms of leasing services and also based on the principle of muamalah, namely the origin of muamalah may be done until there is a argument that prohibits it. The research method used in this study is a juridical-normative method. The type of data used in this study is qualitative. Source of data used is primary data in the form of interviews with Bank Syariah Mandiri and Product Operational Standards (SOP). Secondary data sources are obtained from literature in the form of books and other written documents. In this study the author uses data collection techniques by means of documentation, interviews and literature studies. The results of the study researchers conclude: 1) Application of wakalah contract on BSM E-Money products at Bank Syariah Mandiri Bandung Branch Office Ahmad Yani uses a wakalah contract whereby Bank Syariah Mandiri represents its work to partner outlets (merchants) to become representatives in transactions done by the customer. Partner outlets (traders) get rewards (wages / fees) from each transaction made by the customer for their work. 2) The form and process of BSM E-Money products can be used in various transactions at partner outlets (traders) that already have E-Money marks and can receive various transactions such as top-up, shopping transactions and payment transactions. 3) The relevance between the wakalah contrct in BSM E-Money products is in accordance with Sharia Economic Law.